A Fluid-Structure Interaction Model for Dam-Water Systems: Analytical Study and Application to Seismic Behavior - Ricardo Faria; Sérgio Oliveira; Ana L. Silvestre (Advances in Mathematical Physics)
We consider a dam-water system modeled as a fluid-structure interaction, specifically, a coupled hyperbolic second-order problem, formulated in terms of the displacement of the structure and the fluid pressure. Firstly, we investigate the well posedness of the corresponding variational formulation using Galerkin approximations, energy estimates, and mollification. Then, we apply the finite element method along with the state-space representation of the discrete problem in order to perform a 3D numerical simulation of Cabril arch dam (Zêzere river, Portugal). The numerical model is validated by comparison with available experimental data from a monitoring vibration system installed in Cabril dam.